Ceramic hydroxyapatite derived from fish scales in biomedical applications: a systematic review - Ibrahim, Mohamed Ahmed; Abdelmonem, Mohamed; Ismail, Norsharina; Razis, Ahmad Faizal; Ch’ng, Soo Ee; Abu Bakar, Md Zuki; Chan, Kim Wei (Andover House, 2024)
The production of fish waste is increasing dramatically, as more than 70% of captured fish require processing before being sold. These enormous amounts of fish by-products are wasted, generating an undesirable environmental impact and a loss of value-added products. Recently, there has been a growing interest in utilizing fish scale waste as a low-cost source to produce natural nano hydroxyapatite (HAp) ceramic growth and sustainability. On 1 April 2023, an electronic search was performed across four major databases (ScienceDirect, ProQuest, Scopus, and PubMed). Among the 1824 articles identified, only 27 met this review’s inclusion criteria. These studies extracted HAp from fish scales and conducted in vitro or in vivo assessments. The in vitro studies demonstrated the non-cytotoxic nature of HAp derived from fish scales and its superior cell viability compared to control or synthetic HAp. Furthermore, histopathological evaluations revealed favorable bioavailability and biological responses. These findings indicate that HAp obtained from natural sources offers an environmentally friendly, sustainable, and cost-effective approach for manufacturing these materials, which are fully utilized for high-commercial purposes. Such materials are promising for biomedical applications, contributing positively to the economy, environment, and overall community well-being.